THE APPLIED OF ARABICA COFFEE (Coffea arabica) AS A MARINATING ADDITIVE FOR ORGANOLEPTIC CHARACTERISTICS OF CATFISH FILETS (Pangasius sp.) - Oktarahdiana, Dwi; Pratama, Rusky Intan; Rostika, Rita; Rostini, Iis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Research on catfish filet marinade using Arabica coffee aimed to determine the best concentration of coffee was acceptable to the panelists. This research was carried out in July 2021 at the Fishery Products Processing Laboratory, FPIK Unpad. The method used in this research was an experimental method with four treatments adding different concentrations of coffee to the catfish filets, namely 0%, 5%, 10%, and 15%. The parameters observed consisted of organoleptic tests which included appearance, aroma, texture, and taste. The results of the research showed that the catfish filet which was marinated using Arabica coffee belonged to the category favored by the panelists. The treatment with 15% coffee concentration was preferred with a median value of appearance 7 (preferred), aroma 7, texture 7, and taste 7. Based on the Bayes method for decision making, that the panelists chose taste as an important parameter in receiving the catfish filet which was marinated using coffee, followed by aroma, texture, and appearance.